2017
DOI: 10.1371/journal.pone.0182197
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni reinfection: Analysis of risk factors by classification and regression tree (CART) modeling

Abstract: Praziquantel (PZQ) is an effective chemotherapy for schistosomiasis mansoni and a mainstay for its control and potential elimination. However, it does not prevent against reinfection, which can occur rapidly in areas with active transmission. A guide to ranking the risk factors for Schistosoma mansoni reinfection would greatly contribute to prioritizing resources and focusing prevention and control measures to prevent rapid reinfection. The objective of the current study was to explore the relationship among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The similarity of water contact behaviours between genders is reflected in our epidemiological data presented here, with no significant differences by gender between reinfection risk for SAC. These findings support other epidemiological studies [11,13]. After a period of clearance, egg production is observed less than six weeks later in 37% (n = 20) of the longitudinal cohort.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
See 2 more Smart Citations
“…The similarity of water contact behaviours between genders is reflected in our epidemiological data presented here, with no significant differences by gender between reinfection risk for SAC. These findings support other epidemiological studies [11,13]. After a period of clearance, egg production is observed less than six weeks later in 37% (n = 20) of the longitudinal cohort.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 91%
“…reinfection found that males (children and adults) were more often reinfected between 6 and 12 months after treatment with praziquantel than females (pooled OR: 1.45, p = 0.04 [12]). However, two recent studies looking at reinfection with S. mansoni in school-aged children specifically (ages 6-14 years), in endemic settings in Tanzania and Brazil, found no difference in reinfection between boys and girls at 5, 8 [13], and 12 months [11] after treatment.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, epidemiological considerations and modelling results suggest that a focus on MDA for schoolchildren risks ignoring a potentially substantial reservoir (and morbidity burden) [ 14 , 36 , 75 , 92 , 93 , 103 , 104 ]. Risk factors related to occupation, behavior, and proximity to, as well as dependency on, open water sources have long been identified as challenges to elimination efforts, further underscoring the need to treat also other at-risk populations [ 105 , 106 ] at high coverage [ 92 , 93 , 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…After frequent exposure to parasite antigens, in some individuals, the host immune response can develop resistance to reinfection (McManus et al, 2018). However, reinfection is very frequent in schistosomiasis patients, especially among those living in endemic areas (Dejon‐Agobé et al, 2019; Gazzinelli et al, 2017; Woldegerima, Bayih, Tegegne, Aemero, & Jejaw Zeleke, 2019). The development of resistance or susceptibility to reinfection is influenced by age, pretreatment infection intensity, host immune characteristics, the occurrence of “heavy” infection at baseline, among other factors (Gazzinelli et al, 2017; Mbanefo et al, 2014).…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%